Growth indicators in orthodontic patients. Part 2: comparison of cervical bone age to hand-wrist skeletal age. Relationship with chronological age - (:unkn) unknown (My University, 2010)
AIM: The purpose of this study was to investigate the relationship between hand-wrist skeletal age, chronological age and cervical skeletal age as assessed by lateral cephalometric radiograph. MATERIALS AND METHODS: Lateral cephalometric and left hand-wrist radiographs of 393 Caucasian children from 8 to 18 years old were evaluated. On the hand-wrist radiographs average values of the children's skeletal age as described by Schopf (1978), based on the classification of Bjork (1972), Grave and Brown (1976) were used. Cervical vertebral bone age also was depicted, using the method described by Mito, Sato, and Mitani. Pearson correlation coefficients (r) and regression analysis were calculated to assess the linear relationship between chronological, cervical bone and hand-wrist skeletal age. RESULTS: The cervical skeletal age correlated significantly with both the chronological and the hand-wrist skeletal age for each gender. However, the correlation coefficient between cervical skeletal age and hand-wrist skeletal age for both females (r 0.81) and males (0.76) is higher than that between cervical skeletal age and chronological age (females r 0.73; males r 0.72). In addition, regression analysis indicates that the relationship between cervical skeletal age and hand-wrist skeletal age is stronger than the relationship between cervical skeletal age and chronological age for both sexes. CONCLUSION: Cervical skeletal age reflects skeletal status because it can approximate hand-wrist skeletal age, which is considered to be the most reliable method for measuring the degree of maturity.
Keywords: Female; Humans; Adolescent; Male; Child; Cephalometry; Age Factors; Regression Analysis; Chi-Square Distribution; Malocclusion; Statistics, Nonparametric; Age Determination by Skeleton; Cervical Vertebrae; Hand Bones